ANALISIS PENANGANAN KOMPLAIN DI PT PERUSAHAAN LISTRIK NEGARA (PERSERO) RAYON GOMBONG - Aprilia Dian Salsabila; Endang Larasati; Mochammad Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Complain is a part of service for the custumor when they found unpleasent experience when using the service. Most of the complain that usually stated to PT PLN (Persero) Rayon Gombong is about technical issue. The complain from the custumors usually use for success measurement for PT PLN (Persero) Rayon Gombong in giving service. This research will elaborate and analyse more on how PT PLN (Persero) Rayon Gombong to handle a complain. From research result it showed that PT PLN (Persero) Rayon Gombong had not optimally implement their service in handling a complain. This problem appeared because lack of transparancy in handling complain from PT PLN (Persero) Rayon Gombong to the customors. The other obstacles that appeared were weather and geographically bad location which influenced to the complain handling process. Thus, to handle the problem the recommendation for PT PLN (Persero) Rayon Gombong is to be more transparant to the customer so there will be more complain in the future.